No difference in dose distribution in organs at risk in postmastectomy radiotherapy with or without breast implant reconstruction - Liljegren, Annelie (BioMed Central, 2014)
The aim of this study was to quantify the variation in doses to organs at risk (ipsilateral lung and heart) and the clinical target volume (CTV) in the presence of breast implants. In this retrospective cohort study, patients were identified through the National Breast Cancer Register. Consecutive breast cancer patients undergoing mastectomy between 2009 and 2011 and completing a full course of postmastectomy radiotherapy (PMRT) were eligible. All included patients (n = 818) were identified in the ARIA© oncology information system and further stratified for immediate breast reconstruction (IBR+, n = 162) and no immediate breast reconstruction (IBR-, n = 656). Dose statistics for ipsilateral lung, heart and CTV were retrieved from the system. Radiation plans for patients with chest wall (CW) only (n = 242) and CW plus lymph nodes (n = 576) irradiation were studied separately. The outcome variables were dichotomized as follows: lung, V(20Gy) ≤ 30% vs. V(20Gy) > 30%; heart, D(mean) ≤ 5 Gy vs. D(mean) > 5 Gy; CTV, V(95%) ≥ median vs. V(95%) < median. In the univariate and multivariate regression models no correlation between potential confounders (i.e. breast reconstruction, side of PMRT, CW index) and the outcome variables was found. Multivariate analysis of CW plus lymph nodes radiation plans, for example, showed no association of breast reconstruction with dosimetric outcomes in neither lung nor heart- lung V(20Gy) (odds ratio [OR]: 0.6, 95%CI, 0.4 to 1.0, p = 0.07) or heart D(mean) (OR: 1.2, 95%CI, 0.5 to 3.1, p = 0.72), respectively. CTV was statistically significantly larger in the IBR+ group (i.e. included breast implant), but no correlation between the implant type and dosimetric characteristics of the organs at risk was revealed. In the current study, the presence of breast implants during postmastectomy radiotherapy was not associated with increased doses to ipsilateral lung and heart, but CTV definition and its dosimetric characteristics urge further evaluation.